Exploring Work Readiness Key Factors Among Industrial Chemistry Students in Vocational High Schools - Harjono Harjono; Atikah Alya Farhanah; Endang Susilaningsih; Sri Susilogati Sumarti (Universitas Pendidikan Mandalika (UNDIKMA), 2024)
The research aims to analyze the correlation between motivation, learning quality, critical thinking skills, industrial work practice quality, and vocational readiness of Industrial Chemistry students at vocational high schools (SMK). The research employs a quantitative approach with a survey method. The research used purposive sampling from industrial chemistry students in Central Java, with a sample consisting of 63 students in grade XI. Data collection is done through questionnaires and tests, then analyzed using Structural Equation Modeling - Partial Least Squares (SEM–PLS). The research results show that vocational readiness is directly influenced by learning quality and industrial work practice quality, while learning quality influences the quality of industrial work practice. The results of indirect influence analysis show that the quality of industrial work practice mediates the influence of learning quality on vocational readiness. In this study, the motivation and critical thinking skills of students are not proven to have an effect on vocational readiness, both directly and indirectly. Schools are advised to optimize the quality of learning and the quality of industrial work practice through industry collaboration and cooperation with higher education institutions (HEIs). The motivation and critical thinking skills of students should also be considered to play a role in their vocational readiness.